Social Media Influence on First-Time Voters’ Participation in Digital Democracy - Christabella Angelina WIDJAYA; Hilda Yunita WONO (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to investigate the influence of social media on political participation among first-time voters, focusing on students from the Faculty of Communication at a private university in East Java during the 2024 Presidential Election. Utilizing a quantitative descriptive method, the research involved 143 respondents selected through purposive sampling based on specific criteria. Data was collected via a structured questionnaire and analyzed using a simple linear regression model. The findings revealed a statistically significant positive relationship between social media usage and political participation, expressed through the regression equation Y = 3.011 + 0.290X. The R² value of 0.097 indicates that social media contributes to 9.7% of the variation in political participation. These results support the Stimulus-Organism-Response (SOR) theory, suggesting that social media acts as an effective stimulus that shapes young voters' political attitudes and behaviors. The study emphasizes the strategic role of social media in fostering civic engagement among youth and suggests further research on content types and platform dynamics that drive participation.